(untitled) (American Journal of Islam and Society, 2011)
This article delves into Professor al Faruqi’s understanding of the role of Islamic Ummah as being the ummatan wasatan ‒ “the median among the peoples of mankind” (Qur’an 2:143). For Professor al Faruqi, the concept of al-wasatiyyah (the middle way) explicates the concept of al-tawazun (Islamic balance and “golden means”). This mode of Islamic moderation as stressed by Professor al Faruqi is today in 2011 employed by the Singaporean Muslim community in its response to the government’s concern about Muslim radicalism in the republic. In this way, they do not stoop to the pressures of the country’s secular or religious authorities to compromise any of their religious convictions or beliefs, however much these were distasteful to the authorities.